Stimulation of endogenous ADP-ribosylation by brefeldin A. - De Matteis, M A (1994)
Brefeldin A (BFA) is a fungal metabolite that exerts profound and generally inhibitory actions on membrane transport. At least some of the BFA effects are due to inhibition of the GDP-GTP exchange on the ADP-ribosylation factor (ARF) catalyzed by membrane protein(s). ARF activation is likely to be a key event in the association of non-clathrin coat components, including ARF itself, onto transport organelles. ARF, in addition to participating in membrane transport, is known to function as a cofactor in the enzymatic activity of cholera toxin, a bacterial ADP-ribosyltransferase. In this study we have examined whether BFA, in addition to inhibiting membrane transport, might affect endogenous ADP-ribosylation in eukaryotic cells. Two cytosolic proteins of 38 and 50 kDa were enzymatically ADP-ribosylated in the presence of BFA in cellular extracts. The 38-kDa substrate was tentatively identified as the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase. The BFA-binding components mediating inhibition of membrane traffic and stimulation of ADP-ribosylation appear to have the same ligand specificity. These data demonstrate the existence of a BFA-sensitive mono(ADP-ribosyl)transferase that may play a role in membrane movements.